Reshaping metropolitan America : development trends and opportunities to 2030 - Nelson, Arhur C. (Metropolitan Planning + Design, 2013)
Nearly half the buildings that will be standing in 2030 do not exist today. That means we have a tremendous opportunity to reinvent our urban areas, making them more sustainable and livable for future generations. But for this vision to become reality, the planning community needs reliable data about emerging trends and smart projections about how they will play out. Arthur C. Nelson delivers that resource in Reshaping Metropolitan America. This unprecedented reference provides statistics about changes in population, jobs, housing, nonresidential space, and other key factors that are shaping the built environment, but its value goes beyond facts and figures. Nelson expertly analyzes contemporary development trends and identifies shifts that will affect metropolitan areas in the coming years. He shows how redevelopment can meet new and emerging market demands by creating more compact, walkable, and enjoyable communities. Most importantly, Nelson outlines a policy agenda for reshaping America that meets the new market demand for sustainable places.